Factors Determining Performance of Institutional Schools in Chitwan, Nepal - Adhikari, Dipak Bahadur; Aryal, Gita Nath (Economic Journal of Development Issues, 2019)
Improvement of quality of education is a challenging task; however, it is not impossible. Measuring the performance of schools is not straightforward. In general, number of students passed in the examination in terms of percentage is considered as performance of the schools. Knowing the factors to determine the performance of schools provides some ideas on how to improve the quality of education. The paper, therefore, seeks to show factors that affect performance of the institutional school. The data were collected using structured questionnaires and interview from 90 respondents of Chitwan district, Nepal. The performance of the schools is measured in terms of per cent of students passed in school leaving certificate examination. Improvement in library and laboratory facilities, parents-teacher interactions, drinking water and toilet facilities compared to previous level, and academic quality perceived by teachers determine the performance of the school. Some levels of improvement in playground and sports materials have power to improve the performance of the schools.